EFEKTIVITAS PENGGUNAAN MULTIMEDIA INTERAKTIF DALAM PEMBELAJARAN TERHADAP KEMAMPUAN KOGNITIF SISWA KELAS V SEKOLAH DASAR - Vinky Tri Oktariani; Tri Joko Raharjo; Sarwi; Decky Avrilianda; Bambang Subali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study seeks to evaluate the efficacy of PowerPoint-based interactive multimedia in enhancing the cognitive skills of fifth-grade primary pupils. A quantitative experimental methodology employing a one-group pretest-posttest design is utilised. Tests are a data collection method applied in research. Data analysis through descriptive statistics and inferential statistics. The subject of this research is class V of SDN 26 Talang Ubi. The research results showed that the average score for the pretest of students' cognitive abilities = was 69.25, and the posttest for students' cognitive abilities = was 81.75. These results show that there has been an increase in students' cognitive abilities after using interactive multimedia in learning in class V of SD Negeri 26 Talang Ubi. The N-Gain test obtained an average score of 0.3913, which is in the medium category. In conclusion, the use of interactive multimedia has a significant influence on students' cognitive abilities, but its effectiveness is still relatively moderate.